Fintech Adoption among College Students in Batam, Indonesia: The Influence of Ease of Use and Usefulness - C. Candy; Stephen Huang; Johny Budiman (Golden Ratio of Finance Management, 2026)
Fintech still has significant room for growth, but industry competition is becoming increasingly challenging. To increase fintech adoption, companies must understand individual behavior. This study aims to examine perceived ease of use (PEOU) and perceived usefulness (PU) as central factors that may impact fintech adoption (FA) among college students, a group with a high likelihood of fintech use. This study adopts a quantitative approach, with data collected via a questionnaire distributed to 364 Indonesian college students. Data processing and analysis were performed with Partial Least Squares-Structural Equation Modeling (PLS-SEM). The findings reveal that PEOU positively affects FA among students, both directly and indirectly through PU. In addition, PEOU enhances PU, thereby positively influencing FA. Easy-to-use fintech services help students recognize their practical benefits, thereby encouraging quick adoption. These results suggest that fintech companies targeting college students should prioritize user-friendly design, relevant features, and marketing messages that emphasize ease of use and real benefits to enhance adoption.